An exploratory study of the determinants of information technology hardware production: a country-level analysis. Issue 2 (3rd April 2019) - Shin, Namchul; Dedrick, Jason
ABSTRACT: This research examines empirically factors influencing IT hardware production by employing a country-level data set for 1985–2009. Our results show that IT hardware production is driven by various country-level factors, but the impacts of these factors differ for two types of IT hardware. Electronic data processing (EDP) production has shifted to low GDP countries where wage levels are low, and a large portion of EDP produced in these countries tend to be exported to high GDP countries where demand is high. While the gap has decreased, however, medical and industrial equipment (MIE) production is still largely done in advanced economies. These findings imply that losing the manufacturing base in the U.S. might not be an issue for certain types of products, such as EDP, but it could be a serious issue for MIE. Thus, policies must be industry specific; a 'one-size-fits-all' policy would not work for the global IT industry.